Draft Annual Plan 1979-80 (Centrally sponsored and Central Schemes) Government of Goa, Daman and Diu - Planning Commission (Planning Commission, 1978)
A financial outlay of Rs. 11.11 crores is envisaged for the Centrally Sponsored Schemes in the Five Year Plan, 1978-83. The approved allocation for the year 1978-79 was Rs. 1.96 crores. For the year 1979-80, the envisaged outlay comes to Rs. 2.46 crores.
Government of Goa, Daman and Diu